Adoption and Integrating Industrialised Construction Technology to Small and Medium Construction Enterprises in Tanzania - R. S. Tekka (Journal of Applied Sciences and Environmental Management)
Industrialization has recently eased and cleared the path to mitigate numerous challenges within the construction industry as a consequence of adopting and integrating industrialized construction technologies. Hence, the objective of this paper was to develop a framework of critical strategies towards adoption and integration of industrial construction Technologies to Small and medium Construction Enterprises (SMCE) in Tanzania. Using a structured questionnaire, one-hundred-fifty-nine questionnaires well attended were administered through online media to experienced construction industry professionals. The findings acknowledged nine motivational factors and twelve critical factors including promoting the use of BIM to enhance collaboration and ease communication between project participants, developing educational and training initiatives pertaining to ICT for developers, contractors, and policy makers; Optimization of local building materials usage, and promoting Rand D that geared towards the application of ICT. This study provides fundamental insights for future research in this field aimed at informing the construction industry about the importance of adopting ICT in the construction projects.